2012
DOI: 10.1002/jms.3063
|View full text |Cite
|
Sign up to set email alerts
|

Study of the fragmentation of arginine isobutyl ester applied to arginine quantification in Aedes aegypti mosquito excreta

Abstract: It has been demonstrated that argininolysis and uricolysis are involved in the synthesis and excretion of urea in Aedes aegypti female mosquitoes. To further investigate the metabolic regulation of urea in female mosquitoes, it is desirable to have a rapid and efficient method to monitor arginine (Arg) concentration in mosquito excreta. Thus, a procedure currently used for the identification of Arg in urea cycle disorders in newborn babies was adapted to analyze Arg in A. aegypti excreta. The fragmentation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…This increased a 2 ion intensity suggests that its stability is enhanced, possibly due to a fivemembered cyclic structure [34][35][36]. A strong a 2 -NH 3 ion may result from an increased stability of the arginine side chain forming a seven-membered ring with the N-terminus [37].…”
Section: Peptides With An N-terminal Argininementioning
confidence: 99%
See 1 more Smart Citation
“…This increased a 2 ion intensity suggests that its stability is enhanced, possibly due to a fivemembered cyclic structure [34][35][36]. A strong a 2 -NH 3 ion may result from an increased stability of the arginine side chain forming a seven-membered ring with the N-terminus [37].…”
Section: Peptides With An N-terminal Argininementioning
confidence: 99%
“…The intensities for the aromatic immonium (blue) and a-type (red) ions at each position. The peptides with four aromatic residues (1-4) are in the left charts, and those with one aromatic residue (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) are in the right by losing ammonia [37]. When arginine is at the N-terminus, the average relative abundance of the 112 Da peak is 41%, and at the C-terminus, the abundance is 13%.…”
Section: Aromatic Residues At N-or C-terminusmentioning
confidence: 99%
“…Mosquito excreta were collected as previously described (9). For 6, 12, 18, and 24 h time points, mosquito excreta were collected by removing the female and storing the vial.…”
Section: Preparations Of Extracts For Uric Acid and Heme Assaysmentioning
confidence: 99%
“…The term ammonia is defined here as NH 3 or NH 4 + or a combination of both. The application of isotopically labeled compounds and mass spectrometry, as well as RNA interference (RNAi), has demonstrated that A. aegypti females efficiently detoxify ammonia through 3 phases: fixation, assimilation, and excretion (5)(6)(7)(8)(9)(10). During this complex metabolic challenge, female mosquitoes synthesize specific amino acids, such as Gln, Glu, Ala, and Pro, through reactions catalyzed by several enzymes, including glutamine synthetase, glutamate synthase, glutamate dehydrogenase, pyrroline-5-carboxylate synthase, pyrroline-5-carboxylaye reductase, and alanine aminotransferase (ALAT).…”
mentioning
confidence: 99%
“…By feeding A. aegypti females with isotopically-labeled 15 N-compounds (such as 15 NH 4 Cl), we discovered that mosquitoes have an extraordinary biochemical machine to efficiently detoxify ammonia. Indeed, they synthesize specific amino acids and excrete several nitrogen wastes through multiple metabolic pathways [6-9]. By using this strategy, female mosquitoes are able to survive toxic ammonia concentrations released during the digestion of a blood meal.…”
Section: Introductionmentioning
confidence: 99%